Intracellular self-assembly and metabolite analysis of key enzymes for L-lysine synthesis based on key components of cellulosomes - Li, Nan; Du, Bowen; Ren, Xiankun; Yang, Lu; Du, Peng; Li, Piwu; Wang, Jianbin; Li, Junlin; Xiao, Jing; Wang, Junqing; Wang, Ruiming (Frontiers in Microbiology, 2025)
IntroductionCellulosome is a natural multi-enzyme complex in the extracellular space of anaerobic microorganisms, which has the advantages of small molecular weight, multiple binding sites, and strong designability. This study aimed to explore the influence of intracellular self-assembly complexes on L-lysine biosynthesis.MethodsTwo novel L-lysine-engineered bacteria modification strategies were designed, considering the L-lysine biosynthesis pathway using DocA-S3/Coh as an efficient intracellular assembly element: pairwise assembly of key enzymes in cells and multi-enzyme assembly based on scaffolding proteins. Seven strains of key enzyme pairwise-assembled engineered bacteria were constructed, and four strains of multi-enzyme-assembled engineered bacteria were designed based on the scaffold protein genome.ResultsThe production of L-lysine by multi-enzyme-assembled engineered strain Escherichia coli QDE-aspC-DocA-S3-lysC:pET-28a-ScaA was 46.9% higher than that of E. coli QDE, and the conversion rate was increased from 50.9 to 59.8%. By combining specific analyses with metabolomics, 40 core metabolites of the assembled engineered bacteria were identified and mapped to L-lysine-related metabolic pathways, and the mechanism of how intracellular multi-enzyme assembly promoted the efficient synthesis of multiple amino acids was analyzed.ConclusionThis strategy exerts the “proximity effect” among multi-enzyme complexes, improves the transfer efficiency of intermediate metabolites between different catalytic active centers, indirectly improves the catalytic rate of each key enzyme, and provides a novel idea and technical platform for other multi-enzyme intracellular assemblies.